Stability analysis of backward uncertain differential equations. Issue 2 (3rd April 2019) - Wang, Xiao; Ning, Yufu
ABSTRACT: Backward uncertain differential equation is a class of uncertain differential equations with a terminal value. This paper focuses on its stability analysis. At first, this paper gives the concepts of stability in measure, stability in mean and stability in p th moment for backward uncertain differential equations. In addition, some sufficient conditions in the form of theorem for backward uncertain differential equations being stable in measure, in mean and in p th moment are derived. Meanwhile, this paper further discusses the relationship between these three types of stability.